A Reliable and Non-destructive Method for Monitoring the Stromal pH in Isolated Chloroplasts Using a Fluorescent pH Probe - Su, Pai-Hsiang; Lai, Yen-Hsun (Frontiers in Plant Science, 2017)
The proton gradient established by the pH difference across a biological membrane is essential for many physiological processes, including ATP synthesis and ion and metabolite transport. Currently, ionophores are used to study proton gradients, and determine their importance to biological functions of interest. Because of the lack of an easy method for monitoring the proton gradient across the inner envelope membrane of chloroplasts (pHenv), whether the concentration of ionophores used can effectively abolish the pHenv is not proven for most experiments. To overcome this hindrance, we tried to setup an easy method for real-time monitoring of the stromal pH in buffered, isolated chloroplasts by using fluorescent pH probes; using this method the pHenv can be calculated by subtracting the buffer pH from the measured stromal pH. When three fluorescent dyes, BCECF-AM (2',7'-bis-(2-carboxyethyl)-5-(and-6)-carboxyfluorescein acetoxymethyl ester), CFDA-SE (5(6)-carboxylfluorescin diacetate succinimidyl ester) and SNARF-1 carboxylic acid acetate succinimidyl ester were incubated with isolated chloroplasts, BCECF-AM and CFDA-SE, but not the ester-formed SNARF-1 were taken up by chloroplasts and digested with esterase to release high levels of fluorescence. According to its relatively higher pKa value (6.98, near the physiological pH of the stroma), BCECF was chosen for further development. Due to shielding of the excitation and emission lights by chloroplast pigments, the ratiometric fluorescence of BCECF was highly dependent on the concentration of chloroplasts. By using a fixed concentration of chloroplasts, a highly correlated standard curve of pH to the BCECF ratiometric fluorescence with an r-square value of 0.98 was obtained, indicating the reliability of this method. Consistent with previous reports, the light-dependent formation of pHenv can be detected ranging from 0.15 to 0.33 pH units upon illumination. The concentration of the ionophore nigericin required to collapse the ΔpHenv was then studied. The establishment of a non-destructive method of monitoring the stromal pH will be valuable for studying the roles of the pHenv in chloroplast physiology.